Risks and Resilience of Collaborative Networks : 16th IFIP WG 5.5 Working Conference on Virtual Enterprises, PRO-VE 2015, Albi, France, October 5-7, 2015, Proceedings /: 16th IFIP WG 5.5 Working Conference on Virtual Enterprises, PRO-VE 2015, Albi, France, October 5-7, 2015, Proceedings. (2015) - Unknown
No abstract available